Systematic approach to solving hydrogeology problems in regions with repeated crop crop (in the example of Kashkadarya region) (Acta Education, 2024)
The study discusses the problem of describing an object as a complex system to apply mathematical modeling in the study of changes in groundwater levels as a result of irrigation in areas under repeated cultivation. Testing for the reliability and accuracy of theoretical, technological, methodological and software developments on the optimal state of groundwater in irrigated areas, creating mathematical and simulation models for solving hydrogeological and engineering-geological problems in hydrogeological systems based on various practical methods, In turn, attention is focused on mathematical modeling of geofiltration processes taking into account natural geological and hydrogeological conditions and the formation and solving of specific problems taking into account man-made conditions.